2017
DOI: 10.4103/aer.aer_22_17
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy of dexamethasone added to ropivacaine in transversus abdominis plane block for transabdominal hysterectomy under subarachnoid block

Abstract: Background and Aims:Ultrasound-guided transversus abdominis plane (TAP) block has been proven as a safe and effective analgesic technique for several lower abdominal surgeries. Various adjuvants have been used to intensify the quality and prolong the local anesthetic effect. We evaluated the analgesic efficacy of dexamethasone addition to ropivacaine in TAP block following open abdominal hysterectomy.Materials and Methods:After clearance from the Institutional Ethics Committee, a double-blind, prospective, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 23 publications
7
31
0
Order By: Relevance
“…The literature search identified 354 studies, including 9 qualifing RCTs with a total of 575 patients that met the inclusion criteria ( Fig 1 ) [ 16 , 17 , 24 30 ]. The characteristics of patients and interventions are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search identified 354 studies, including 9 qualifing RCTs with a total of 575 patients that met the inclusion criteria ( Fig 1 ) [ 16 , 17 , 24 30 ]. The characteristics of patients and interventions are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All 9 RCTs compared the TAP block using LA with dexamethasone versus LA alone. All studies used a long-acting LA for the TAP block, including bupivacaine in 3 studies [ 26 , 28 , 29 ], ropivacaine in 5 studies [ 16 , 17 , 24 , 25 , 30 ], and levobupivacaine in 1 study [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-operative VAS pain scores were significantly lower at 4, 6, and 12 h in Group Ropivacaine Dexamethasone (RD) as compared to Group Ropivacaine (R) alone (p<0.05). Significantly longer analgesia (13.2±7.6 vs. 7.1±4.6 h, p<0.001) with lesser tramadol requirement in first 24 h (50.2±34 vs. 94±35 mg, p<0.001) were observed in Group RD as compared to Group R. 23 Dexamethasone 300 µg/kg with ropivacaine intraarticular has a superior analgesic efficacy a much prolonged postoperative pain relief, minimal post-operative analgesia requirement and better patient compliance with negligible side effects. Liu et al did a prospective observational study and used a single shot of bilateral thoracic paravertebral block (TPVB) with 25 ml of 0.2% ropivacaine and 5 mg dexamethasone in combination for both sides at the 8 th thoracic transverse level (T8) performed on 201 participants who complained moderate to severe pain on arrival to postanesthesia care unit (PACU) after laparotomy.…”
Section: Perineural Dexamethasonementioning
confidence: 83%
“…14 Similarly, TAP block with Dex-R combination was associated with lower VAS score 12 hours after surgery, longer time to first tramadol use, and total tramadol use when compared with ropivacaine alone after abdominal hysterectomy. 15 However, another study showed that TAP block with Dex-R and ropivacaine did not differ in terms of postop pain score after inguinal hernia repair and spermatocelectomy. 16…”
Section: Discussionmentioning
confidence: 96%